Biventricular amputation for biventricular pulsatile assist device implantation in patients with severe ventricular septal perforation - Vollroth, Marcel (Oxford University Press, 2013)
Complete ischaemic destruction of the cardiac apex as well as the majority of the ventricular septum is usually a lethal condition with no alternatives except mechanical circulation support and highly urgent heart transplantation. Depending on the mass of the necrotic and destructed myocardium, implantation of a ventricular assist device can be challenging due to insufficient tissue quality. We describe here a new approach to pulsatile Thoratec (Thoratec Corporation, Pleasanton, CA, USA) extracorporeal biventricular assist device implantation.